Essential roles of B cell subsets in the progression of MASLD and HCC - Nataliia Petriv; Huizhen Suo; Inga Hochnadel; Kai Timrott; Nina Bondarenko; Lavinia Neubert; Elena Reinhard; Nils Jedicke; Patrick Kaufhold; Carlos Alberto Guzmán; Ralf Lichtinghagen; Michael P. Manns; et al. (JHEP Reports)
Background & Aims: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death. Metabolic dysfunction-associated steatotic liver disease (MASLD) is a significant cause of HCC. Current treatment options for HCC are very limited. Recent evidence highlights B cells as key drivers in MASLD progression toward HCC. However, it remains unclear whether multiple B cell populations or a distinct B cell subset regulates inflammatory responses during liver disease progression. The scope of this study was to define protumorigenic B cell subsets in MASLD and HCC. Methods: Multicolor flow cytometry, immunohistochemistry, and immunofluorescence analyses were performed to investigate B cell populations locally (in liver tissue) and systemically (in the blood) in mice with MASLD (n = 6) and HCC (n = 5–6). The results obtained in mice were also verified in patients with MASLD (n = 19) and HCC (n = 16). Results: Our study revealed an increase of two regulatory B cell (Breg) subsets, CD19+B220+CD5+CD1d+ (p <0.0001) and CD19-B220+CD5+CD1d- (p <0.0001), both of which highly overexpress IgM/IgD, PD-L1, and IL-10, in the livers of mice with MASLD and HCC. Furthermore, we showed that B-cell depletion therapy in combination with a Listeria-based vaccine decreased CD19-B220+CD5+CD1d- Bregs (p = 0.0103), and improved survival of mice with HCC. We also found CD19+CD5+IL-10+ (p = 0.0167), CD19+CD5+PD-L1+ (p = 0.0333) and CD19+CD5+IgM+IgD+ (p = 0.0317) B cells in human HCCs. In addition, strong overexpression of IgM/IgD, PD-L1, IL-10, were detected on non-switched memory B cells (p = 0.0049) and plasmablasts (p = 0.0020). The examination of blood samples obtained from patients with MASLD showed an increase of total B cells expressing IL-10 (p <0.0001) and IgM/IgD (p = 0.3361), CD19+CD20+CD5+CD1d+ Bregs (p = 0.6424) and CD19+CD20+CD27+ non-switched memory B cells (p = 0.0003). Conclusions: Our results provide novel insights into the protumorigenic roles of several B cell subsets, the specific targeting of which could abrogate the progression of liver disease. Impact and implications: Hepatocellular carcinoma (HCC) is the primary liver cancer with a constantly rising mortality rate. Metabolic dysfunction-associated steatotic liver disease (MASLD) is an emerging important cause of HCC. Current treatment options for HCC are limited and there is a high risk of recurrence. The study aims to identify new therapeutic strategies by exploring the immunological aspects of MASLD and HCC. Our findings extend the current knowledge on the role of B cells in the progression of MASLD and HCC. This study emphasizes the involvement of IgM+IgD+ regulatory B cells (Bregs) in malignant liver disease progression. These Bregs characterized by a high expression of PD-L1, IL-10, IgM, and IgD. Two other B cell subsets with immunosuppressive phenotype have been found in the study in murine liver disease - plasmablasts and non-switched memory B cells. Targeting these B cells could lead to more effective treatments of HCC.